The Association between Parenting Styles and Behavioral Problems in Children - Charoenjit , Suppanat; Ngernlangtawee, Dussadee (Vajira Medical Journal : Journal of Urban Medicine, 2021)
Background: Behavioral problem was the common problem that had long-term effects on child’s performance. This study aimed to investigate the association between parenting style and child behavioral problems. Methods: A cross-sectional study was conducted by using parenting style questionnaire and strengths and difficulties questionnaire (SDQ) to collect data from caretaker of children, aged 3-15 years old who were treated at Vajira Hospital. The prevalence of parenting styles and association between parenting styles and behavioral problems in children were analyzed by multiple linear regression. Results: 198 participants were enrolled. Male caretaker was 52%, mean age was 38.45 ± 11.6 years old. Boy was 55.6%, mean age was 8.19 ± 2.72 years old. The prevalence of authoritative, permissive and authoritarian parenting style was 59.6%, 23.2% and 17.2%, respectively. The study showed significantly difference of total difficulties score among parenting style groups (p-value = 0.034). Linear regression analysis showed difficult or slow-to-warm up temperament ( = 0.196, t = 2.805, p-value = 0.006), birth order ( = -0.145, t = -2.052, p-value = 0.041) and authoritarian parenting style ( = -0.149, t= -2.106, p-value = 0.036) were factors that impact to child’s total difficulties score. When cofactor was controlling, difficult or slow-to-warm up temperament ( = 0.20, 95% CI = 0.96-3.62, p-value = 0.004) and birth order ( = -0.15, 95% CI= -1.84,-0.06, p-value = 0.037) were factors that still be a great impact significantly. Conclusions: The most common parenting style was authoritative style. Parenting styles were associated with child behavioral score. Temperament and birth order were factor that impact to behavioral score.